Aktivisme Islam di Sekolah Menengah Atas : Perkembangan Terkini di Indonesia - Amin Mudzakkir (Societas Dei: Jurnal Agama dan Masyarakat, 2023)
This study examines the latest developments in Islamic activism in Indonesia's high schools. Using the theoretical framework of Islamic social movements from Wictorowitz, the main research questions include: (1) what government policies influence Islamic activism? (2) How is the Islamic activism network built? (3) what narratives do they develop? This study uses case studies conducted at SMAN 51 Jakarta and SMAN 31 Jakarta. By conducting interviews with 15 sources, observations, and relevant literature studies, this study shows the influence of educational policies, especially the 2013 curriculum, on forming Islamic activism in high schools. Furthermore, this activism creates rohis (rohani Islam) networks that connect students with the world outside school. Within this network, a narrative framing about piety continues to change according to broader constellations. This study recommends that Islamic activism in secondary schools be understood comprehensively as a social movement, more than just part of religious conservatism, to handle it more appropriately.